Effects of Metabolic Syndrome on Language Functions in Aging. (6th February 2015) - Cahana-Amitay, Dalia; Spiro, Avron; Cohen, Jason A.; Oveis, Abigail C.; Ojo, Emmanuel A.; Sayers, Jesse T.; Obler, Loraine K.; Albert, Martin L.
Abstract: This study explored effects of the metabolic syndrome (MetS) on language in aging. MetS is a constellation of five vascular and metabolic risk factors associated with the development of chronic diseases and increased risk of mortality, as well as brain and cognitive impairments. We tested 281 English-speaking older adults aged 55–84, free of stroke and dementia. Presence of MetS was based on the harmonized criteria (Alberti et al., 2009 ). Language performance was assessed by measures of accuracy and reaction time on two tasks of lexical retrieval and two tasks of sentence processing. Regression analyses, adjusted for age, education, gender, diabetes, hypertension, and heart disease, demonstrated that participants with MetS had significantly lower accuracy on measures of lexical retrieval (action naming) and sentence processing (embedded sentences, both subject and object relative clauses). Reaction time was slightly faster on the test of embedded sentences among those with MetS. MetS adversely affects the language performance of older adults, impairing accuracy of both lexical retrieval and sentence processing. This finding reinforces and extends results of earlier research documenting the negative influence of potentially treatable medical conditions (diabetes, hypertension) on language performance in aging. The unanticipated finding that persons with MetS were faster in processing embedded sentences may represent an impairment of timing functions among older individuals with MetS. ( JINS, 2015, 21, 116–125)